2020
DOI: 10.3390/w12010134
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Framework for Assessing the Energy Efficiency in Urban Water Systems and Its Demonstration in the Portuguese Water Sector

Abstract: Urban water systems (UWSs) are energy-intensive worldwide, particularly for drinking-water pumping and aeration in wastewater treatment. Usual approaches to improve energy efficiency focus only on equipment and disregard the UWS as a continuum of stages from source-to-tap-to-source (abstraction/transport—treatment—drinking water transport/distribution—wastewater and stormwater collection/transport—treatment—discharge/reuse). We propose a framework for a comprehensive assessment of UWS energy efficiency and a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The benefits of pursuing joint water and energy efficiency for water services providers are outlined in [6,8] for Portugal, Romania [48] and Italy [49]. Such efforts lead to saving not only water and the associated energy input but also reductions in the energy costs and energy demand associated with water losses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of pursuing joint water and energy efficiency for water services providers are outlined in [6,8] for Portugal, Romania [48] and Italy [49]. Such efforts lead to saving not only water and the associated energy input but also reductions in the energy costs and energy demand associated with water losses.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance schedules were mostly scheduled on monthly basis. The first question posed in the selection of the WSPs as suggested in [6], was: is energy efficiency an issue for the WSPs and if so, is it likely to be an issue of major concern as water demand grows? This was an important reflection since some WSPs are largely gravity-fed, with relatively low energy costs compared to their total operational costs.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…PIs are expressed by the ratio between two variables of the same nature. In essence, the numerator expresses the objective of the indicator (e.g., real losses, network failures), and the denominator represents a related system scale (e.g., network length) (Loureiro et al, 2020). The PIs are calculated for a reference period, generally one year, and the value found does not issue judges, requiring comparison with a reference.…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…For the wastewater subsector, existing studies are limited and tend to concentrate on individual assets, such as wastewater treatment facilities [16,17] or pumping stations [18,19], with very few existing developments centred on the integrated analysis of energy efficiency in the wastewater system as a whole. A recent study [20] analysed the energy use and efficiency in this subsector integrated in a broad urban water-cycle analysis. For the few specific studies found, none uses a tailored performance assessment system (PAS) to support energy management.…”
Section: Introductionmentioning
confidence: 99%